Results-Based Management Strategy for Phase II (2017-2022): CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
RBM is key to CCAFS’ program management and programmatic accountability towards outcomes and impacts, as it places emphasis on systematic, iterative learning and modification (UNDP 2011). RBM follows the logical causal chain that project activities produce tangible research outputs. The strategic use of these outputs can help transform them into appropriate outcomes (i.e. changes in practice and behavior of key next users, preceded by changes in knowledge, attitude, and skills). By tying the RBM approach to impact pathways as elucidated in theories of change (ToC) at CRP, FP, Region and project levels, CCAFS focuses on people, given that these are the ones who ultimately will change their behavior and thus contribute to developmental impact. This is reflected in CCAFS’s “three thirds” management principle: one-third of programmatic effort goes into engaging with partners to decide what needs to be done and how, one-third into doing cutting-edge research, and one-third into strengthening capacity of next users to use the results of the research to achieve outcomes (Fullana i Palmer et al. 2011).